Teatralidades no espaço escolar: uma investigação com crianças da educação infantil - Larissa Maria Santos Altemar (2018)
The present treatise investigates the theatricalities of young children, in both the early childhood education school routine and the acting class. In the former case we observed the relations that the children establish without any guidance from an adult, while in the latter we surveyed the appropriation of objects during activities guided by the acting teacher. In order to perform such investigation, we took as methodological bases the participant observation and the pedagogical intervention research, first observing and taking part to the school routine, and then performing the pedagogical intervention in the time/space of the acting class. It is remarked that the pedagogical intervention phase was performed together with the acting teacher and based on the analysis of the children experiences in the aforementioned class. Starting from the phase of planning, to the phases of execution and analysis, we perceived that the lines, gestures, and reflections of the children and of the accompanying teacher are the elements that constitute this research. We established dialogs with authors in the area of childhood (CORSARO, 1985,1992, 2002; SARMENTO 2004, 2005, 2008, 2011, VIGOTSKI, 2014, 1988) and theater (ALMEIDA JUNIOR, 2007abc, JAPIASSU, 2003, 2009, LEONARDELLI, 2011, MACHADO 2010abc, 2011, 2012, PUPO, 2001, 2005, 2010, RYNGAERT 2009), aiming to provide different reflections about the theater with young children. We organized the analyses in the two considered contexts, daily school routine and acting class, starting from theatrical elements: narrative, space and action, emphasizing, in the first context, the effect of spaces over creative imagination, and in the second one, the connection with the object involved in games. With this research we perceived the possible dialogues between childhood cultures and the organization of a contemporary theatrical action. These dialogues have become noticeable only through the analysis of young children's relations with spaces and between peers, where we stressed the dramatic theatrical organization, based on the text, since children also demonstrated powerful abilities to dialogue with another way of operating the theatricality. During the pedagogical interventions, we perceived different degrees of appropriation of the object, a consequence of the different goals of the games and also of the individuality of the group members. Each one, being closer to or distant from metaphorical or illustrative elaborations, experienced theatricalities by constructing narratives, spaces and actions in different dimensions by means of the re-signification of the object offered as a motto of creation.